2016
DOI: 10.1111/php.12570
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Photocatalytic Activity of Sr4Al14O25: Eu2+, Dy3+ Persistent Phosphors by Codoping with Bi3+ Ions

Abstract: The photocatalytic activity of Bismuth-codoped Sr Al O : Eu , Dy persistent phosphors is studied by monitoring the degradation of the blue methylene dye UV light irradiation. Powder phosphors are obtained by a combustion synthesis method and a postannealing process in reductive atmosphere. The XRD patterns show a single orthorhombic phase Sr Al O : Eu , Dy , Bi phosphors even at high Bismuth dopant concentrations of 12 mol%, suggesting that Bi ions are well incorporated into the host lattice. SEM micrographs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Although the Bi 3+ dopant significantly quenched LE emission in the Bi 3+ -rich sample, its intensity was still much higher than that of a sample without Bi 3+ . The results confirmed that LE emission was a function of the Bi 3+ dopant, as reported in Bi-lanthanide codoped systems. The PL quenching may due to nonemissive Bi 3+ ions capturing photogenerated electrons from Sb 3+ ions. As shown in Figure e,f and Figure S8, when the Sb 3+ dopant concentration was greater than 1%, the LE emission intensity decreased with increasing Sb 3+ concentration, similar to the Bi 3+ conditions.…”
supporting
confidence: 81%
“…Although the Bi 3+ dopant significantly quenched LE emission in the Bi 3+ -rich sample, its intensity was still much higher than that of a sample without Bi 3+ . The results confirmed that LE emission was a function of the Bi 3+ dopant, as reported in Bi-lanthanide codoped systems. The PL quenching may due to nonemissive Bi 3+ ions capturing photogenerated electrons from Sb 3+ ions. As shown in Figure e,f and Figure S8, when the Sb 3+ dopant concentration was greater than 1%, the LE emission intensity decreased with increasing Sb 3+ concentration, similar to the Bi 3+ conditions.…”
supporting
confidence: 81%
“…Bi 3+ and B 3+ are two kinds of co‐dopants for luminescence tuning, while the conditions need to be carefully chosen. Diaz‐Torres and co‐workers reported that Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ ,Bi 3+ phosphors with different bismuth concentrations always decrease the emission spectra and afterglow time, [ 204 ] which can be attributed to the formed quenching centers. In other systems, like ZnGa 2 O 4 :Cr 3+ ,Bi 3+ , [ 90a ] Ca 3 Ga 2 Ge 3 O 12 :Cr 3+ ,Bi 3+ , [ 172b ] Zn(Ga 1‐x Al x ) 2 O 4 :Cr 3+ ,Bi 3+ , [ 181a ] ZnGa 2 O 4 :Cr 3+ ,B 3+ , [ 205 ] SrAl 2 O 4 :Eu 2+ ,Dy 3+ ,B 3+ , [ 35,206 ] Ca 0.85 Zn 0.15 TiO 3 :Pr 3+ ,B 3+ , [ 152 ] Ca 2 Zn 4 Ti 16 O 38 :Pr 3+ ,B 3+ , [ 79 ] and Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ ,B 3+ , [ 207 ] a certain extent of PL improvements were present, while the mechanisms are divergent, such as the suppression of the self‐reduction effect of Cr 3+ , [ 90a ] formation of the electron traps as the Cr 3+ ‐Bi 3+ couple, [ 172b ] and probably increased depth or concentration of the traps.…”
Section: Afterglow Modulating Methodsmentioning
confidence: 99%
“…[ 202 ] Degradation of toxic materials [ 203 ] such as organic dyes [ 204 ] to some harmless form can be achieved using photocatalysis with LLP materials. Carlos et al [ 205 ] found enhancement in photocatalytic activity due to Bi 3+ codoping. However, this is detrimental for LLP.…”
Section: Aluminate Phosphors For Applicationsmentioning
confidence: 99%